2015
DOI: 10.1007/s11665-015-1458-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Processing Parameters on Microstructure Evolution of Al-7Si-Mg Alloy by Cooling Slope Casting

Abstract: This work investigates the effects of pouring temperature, slope length, and slope temperature in cooling slope casting on the formation of globular microstructure of Al-7Si-Mg alloy. The remnant alloy on the slope during casting was quenched and characterized at different stages of flow to evaluate the microstructure features developed in cooling slope casting. The primary a-Al dendritic phase found in conventional cast alloy was transformed into globular shape in slope-processed cast alloy. Finer and more ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…3 shows the least grain size of 33 lm while having the maximum shape factor which is in accordance with the microstructure. The present finding is in contradiction with most of the previous studies (Table 1) which shows a minimum grain size and maximum shape factor at higher cooling slope angles [4,[11][12][13][14][15]. The experimental investigations by Taghavi et al [11] and Das et al [4,12,15] concluded 40°(slope length of 400 mm) and 60°angle (slope length of 500 mm) to be the optimum cooling slope angle respectively.…”
Section: Microstructural Characterizationcontrasting
confidence: 99%
“…3 shows the least grain size of 33 lm while having the maximum shape factor which is in accordance with the microstructure. The present finding is in contradiction with most of the previous studies (Table 1) which shows a minimum grain size and maximum shape factor at higher cooling slope angles [4,[11][12][13][14][15]. The experimental investigations by Taghavi et al [11] and Das et al [4,12,15] concluded 40°(slope length of 400 mm) and 60°angle (slope length of 500 mm) to be the optimum cooling slope angle respectively.…”
Section: Microstructural Characterizationcontrasting
confidence: 99%
“…The complexity in optimizing the process parameters in cooling slope technique has led many researchers to delve into this domain of optimization of cooling slope technique. Few such investigations have been highlighted [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The DS and PS are commonly influenced by different cooling slope parameters process viz: pouring temperature, pouring distance, and slanting angle. These parameters are the major cooling slope process parameters used to affect billet performance and quality [3][4].…”
Section: Introductionmentioning
confidence: 99%